Logistics Support Strategy as an Operational Force Multiplier by the Army Transportation Service: A Case Study of the 1976 Free Aceh Movement Insurgency - Suhendar, Henri; Dohamid, Ahmad G; Harsono, Gentio (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
The military operation conducted to address the Free Aceh Movement (Gerakan Aceh Merdeka/GAM) insurgency in 1976 required a logistics system capable of ensuring mobility, sustainability, and operational effectiveness of the Indonesian Army. In this context, the Army Transportation Service (Dinas Angkutan Angkatan Darat/DAAD) played a strategic role in supporting combat operations, particularly amid limited infrastructure, difficult geographical terrain, and the dynamics of protracted armed conflict in Aceh. This study aims to analyze both the role and the logistics support strategy implemented by DAAD during Operation Nanggala in 1976.This research employs a qualitative descriptive approach, utilizing interviews, document analysis, and triangulation of data sources. The analytical framework is based on Arthur F. Lykke Jr.’s Ends–Ways–Means strategy model and military logistics theory to examine the alignment between operational objectives, logistical courses of action, and available resources. The findings indicate that DAAD logistics functioned not merely as a technical support element but as a strategic enabler of operational success. DAAD ensured troop mobility, distribution of ammunition and supplies, medical evacuation, and the security of transportation routes. The strategy implemented was adaptive, layered, and coordinated, allowing the maintenance of operational tempo despite geographical and security constraints. This study concludes that military logistics, particularly transportation support, constitutes a strategic foundation for operational effectiveness. Strengthening doctrine, institutional coordination, and adaptive logistics systems is therefore essential for future Indonesian Army operations, both in combat and non-war military missions.